2009
DOI: 10.1111/j.1467-9922.2009.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Language Is a Complex Adaptive System: Position Paper

Abstract: Language has a fundamentally social function. Processes of human interaction along with domain-general cognitive processes shape the structure and knowledge of language. Recent research in the cognitive sciences has demonstrated that patterns of use strongly affect how language is acquired, is used, and changes. These processes are not independent of one another but are facets of the same complex adaptive system (CAS). Language as a CAS involves the following key features: The system consists of multiple agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
206
1
30

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 655 publications
(246 citation statements)
references
References 105 publications
9
206
1
30
Order By: Relevance
“…Previous work has suggested that aspects of language appear to be adapted to ecological or social niches (56). For example, linguistic diversity is correlated with biodiversity (57) and pathogen prevalence (58), and morphological complexity is related to population size (59).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that aspects of language appear to be adapted to ecological or social niches (56). For example, linguistic diversity is correlated with biodiversity (57) and pathogen prevalence (58), and morphological complexity is related to population size (59).…”
Section: Discussionmentioning
confidence: 99%
“…Through a usage-based approach, we can begin to understand the nature of phonology as emergent and dynamic (Beckner et al 2009;Elman 1995;Thelen & Smith 1996). What Embodied Cognitive Phonology adds to well-established frameworks is the inclusion of phonemes in the same echelon as other symbolic units, schematized from usage-events.…”
Section: An Embodied Cognitive Phonologymentioning
confidence: 99%
“…Language appears as a complex information channel (Shannon, 1948), continuously evolving to facilitate communication (more about its complex adaptive nature in Beckner et al, 2009;Ramscar, 2010;Ramsar & Baayen, 2013). Moreover, it unfolds on many levels of granularity, from orthographic and phonological elements, over words and word chunks to sentences and beyond.…”
Section: Discussionmentioning
confidence: 99%